Convexity Dura-Based Cerebral Cavernous Malformation Mimicking Meningioma: A Case Report and Literature Review - Abujarir, Raed Hassan; Ayyad, Ali; Sotouhy, Ahmad; Bozom, Essam; Shaaban, Ahmed; Kubaissi, Aisha Al (Asian Journal of Neurosurgery, 2022)
Cavernous angioma, cavernoma, cavernous hemangioma, also called cerebral cavernous malformation (when present in the brain), are benign vascular malformations, usually intraparenchymal; however, a few reported cases are in the extra-axial location—as middle cranial fossa, near the cavernous sinuses, and in the cerebellopontine angle—and are rarely reported as dura-based convexity lesion resembling meningioma. We report a giant dura-based, convexity, a cerebral cavernous malformation. We wish to notify the case as occurring at a rare location and a large-sized cerebral cavernous malformation. A case of young female presented with a long-standing history of headache. Computed tomography scan and magnetic resonance imagings (MRIs) suggested right occipital dura-based large mass lesion of approximately 5 cm in diameter. The lesion was excised and pathology studies confirmed the diagnosis of a cerebral cavernous malformation. A follow-up MRI confirmed total resection of the lesion and the patient had a smooth postoperative recovery.
Keywords: dura-based cavernous malformation; extra-axial cavernous malformation; cavernoma mimicking meninigioma